Gated Communities – by product of the lack of trust? - Waszkiewicz, Pawel (My University, 2017)
Gated communities are housing areas that have been enclosed in one way or another, typically involving heavy use of surveillance technology (see Addington & Rennison, 2015). Such areas were first described in the USA and South Africa in the late 80s and early 90s (McKenzie, 1994; Blakely & Snyder, 1997). Since then they has been focal points of several research projects in different regions of the world (Low, 2003; Glasze, 2003). There is a significant number of publications covering the increasing number of gated communities in Central and Eastern Europe (CEE) after democratization of formerly communist societies (Bodnar & Molnar, 2009). In the post-communist context, a general lack of trust, the increasing socio-economic polarization, fear of crime and the existential insecurity created in the democratization process have been forwarded as potential explanations for the rapid expansion of gated communities (Hirt & Petrovic, 2010). Paper will present the results of the project Like Fish in Water: Surveillance in Post-Communist Societies that commissioned field work in Estonia, Poland, and Serbia (2014-15). A representative and probabilistic sample of 1000 respondents from each country were interviewed face-to-face on matters of trust, security, surveillance and a range of contextual aspects, among others gated communities.
Keywords: Organización comunitaria